Protection against the Phytotoxic Effect of Mercury Chloride by Catechin and Quercetin - Yedda M. L. S. de Matos; Daniel L. M. Vasconcelos; Antonio C. H. Barreto; Janaína E. Rocha; José B. de Araújo-Neto; Fábia F. Campina; Maria Milene C. da Silva; Tássia T. Al Yafawi; Celestina E. Sobral-Souza; Jacqueline C. A. Pinheiro; Saulo R. Tintino; Amanda K. Sousa; et al. (Journal of Chemistry)
Plants when exposed to toxic levels of metals can suffer morphological or physiological damage because toxic metals can interact with several vital molecules in the plant. One possibility to remove these contaminants from the environment is through the phytoremediation technique, since secondary metabolites produced by plants can reverse these damages. To evaluate the cytoprotective activity, the dry mass and possible damage to the membranes of Lactuca sativa (lettuce) seedlings subjected to different concentrations of mercury chloride in association with catechin and quercetin in suballelopathic concentration were determined. The coordination of mercury chloride with substances was also evaluated using vibrational spectroscopy (Raman and FTIR). The interaction of the mentioned flavonoids with mercury chloride was evidenced through vibrational spectroscopy. When the metal was associated with catechin and quercetin, there was an increase in dry mass of almost 3 times when compared with the HgCl2 alone, demonstrating that these flavonoids act as cytoprotective agents. However, in the presence of catechin and quercetin, membrane damage caused by mercury chloride has a level similar to that observed in control plants, demonstrating none statistical difference. Comparing the highest concentration with the lowest concentration of the metal associated with quercetin, it can be seen that the intensity of the peaks in this region decreases when the concentration of the metal increases, indicating an interaction between the metallic compound and the flavonoid. In this context, the use of secondary metabolites can be an alternative in the process of remediation of areas contaminated by mercury chloride, as they mitigate the effects of mercury chloride on lettuce seedlings.